Meningococcal vaccination for international travellers from Greece visiting developing countries. Issue 3 (May 2016) - Pavli, Androula; Katerelos, Panagiotis; Smeti, Paraskevi; Maltezou, Helena C.
Summary: Background: Meningococcal meningitis is a serious disease. Travel-associated infection for the general traveller is low; however regular epidemics in indigenous population, particularly in sub-Saharan Africa are responsible for significant morbidity and mortality. Our aim was to assess meningococcal vaccination for international travellers from Greece. Methods: A prospective questionnaire-based study was conducted during 2009–2013. Results: A total of 5283 travellers were studied (median age: 39.2 years); Meningococcal tetravalent vaccine (A, C, W135, Y) was delivered to 1150 (21.8%) of them. Of those who travelled to the Middle East and sub-Saharan Africa, 73.1% and 21.2% received meningococcal vaccine, respectively. Of those travellers who travelled to sub-Saharan Africa from November to June and from July to October, 22.1% and 20.6% were vaccinated with meningococcal vaccine, respectively. Of all travellers who travelled for <1 month and ≥1 month, 23.3%, and 20.5%, were vaccinated, respectively. Meningococcal vaccine was administered to 95.3% of pilgrims, 17.4% of those visiting friends and relatives (VFRs), 16.7% of those who travelled for recreation, and 13.8% of those who travelled for work. Of travellers who stayed in urban, in rural, and in urban and rural areas, 32%, 11.6% and 12.7% were vaccinated, respectively. Meningococcal vaccine was delivered to 29.2%, 21.1%, 19.4% and 5.1% of those who stayed in hotels, at local people's home, in camps, and on ships, respectively. The association of meningococcal vaccine administration with the destination, duration and purpose of travel, area of stay and type of accommodation was statistically significant. Conclusion: There is a need to improve meningococcal vaccine recommendations for travellers from Greece, particularly for high risk populations, such as VFRs, business travellers and those visiting sub-Saharan Africa especially during the dry season.